Sirens of Modernity World Cinema via Bombay - Sunya, Samhita (University of California Press, 2022)
By the 1960s, Hindi-language films from Bombay were in high demand, not only for domestic and diasporic audiences, but for sizable non-diasporic audiences across Eastern Europe, Central Asia, the Middle East, and the Indian Ocean world. Confounding critics who saw the films as noisy and nonsensical, Bombay films attracted worldwide viewers precisely for their elements of romance, music, and spectacle. In this richly documented history of 1960s Hindi cinema, Samhita Sunya historicizes the emergence of world cinema as a category of cinematic diplomacy that formed in the crucible of the Cold War. Interwoven with this history is an account of the prolific transnational circuits of popular Hindi films. By following archival leads and threads of argumentation within commercial Hindi films that seem to be odd cases-flops, remakes, low-budget comedies, and prestige productions-this book offers a novel map for excavating the historical and ethical stakes of world cinema and world-making via Bombay. "Samhita Sunya's rich and provocative book offers a needed corrective to contemporary debates on transnational cinema, translation and co-production, and cinephilia by approaching them from a new geographic and historical vantage point. A terrific contribution to a growing body of film studies scholarship that is redefining the field as we know it." Masha Salazkina, author of In Excess: Sergei Eisenstein's Mexico "This elegantly written book remaps the atlas of world cinema. Its refreshingly non-Eurocentric perspective, innovative methods for tracing the intersection of material and affective histories of circulation, and transregional scope make it a valuable addition to film studies, South Asian studies, and inquiries into the global 1960s." Manishita Dass, author of Outside the Lettered City: Cinema, Modernity, and the Public Sphere in Late Colonial India